Comportamento da filtração de gases em meios filtrantes de celulose - Osório, Vanessa Moreira (Universidade Federal de São Carlos, 2006)
The present work aims to evaluate, through filtration process and cake detachment, the behavior of two cellulose fiber filtering media with different air permeability values. The powder material used was phosphatic concentrated rock of density 2,99 g/cm3 and its average volumetric diameter of 8,34 µm. The equipment used was constituted of a circular filter, powder feeder which controlled the massic flow and humidity by a microcomputer and a system for control and acquisition of data. The filtering media used were cellulose fibers, Rad More and Rad Plus, supplied by Alhstrom Louveira. The work was accomplished by a successive sequence of filtration and cleaning during 100 filtration cycles using cellulose filtering media. The technique employed for cake removal was reverse air flow. In the experimental procedure, filtration velocity of 10 cm/s was used for maximum pressure drop of 200 mmH2O, and 5 cm/s for maximum pressure drop of 100 mmH2O. Two cleaning velocity were employed for cake removal, 18 and 13 cm/s. The results showed that the filtering media Rad Plus, when submitted to filtration velocity of 10 cm/s and cleaning velocity of 18 cm/s, obtained the best operational condition, as it presented lower values of residual pressure drop for a larger mass retained during the 100 filtration cycles. For different filtration velocity, 10 and 5 cm/s, the filtering media Rad Plus, more porous and more permeable, the amount of particle mass removed was larger than for the filtering media Rad Plus applying cleaning velocity of 18cm/s as the removal force for this cleaning velocity could remove the particles retained in the fibers. For filtration velocity of 5 cm/s, a lower cleaning velocity, 13 cm/s, was enough to remove larger amount of particles, when compared with the filtering media Rad Plus in the same experimental conditions.
Keywords: Filtração de gases; Meios filtrantes de celulose; Perda de carga residual; Porosidade; ENGENHARIAS::ENGENHARIA QUIMICA